Health Risks from PM2.5, PM10, and TSP Exposure Among Market Workers Around the 16 Ilir Market in Palembang City - Sitanggang, Jhon Wesly (Poltekkes Kemenkes Palu, 2025)
Background: The air quality index of an area can be evaluated by looking at environmental parameters that serve as air quality monitoring standards, including PM2.5, PM10, and TSP. Exposure to these particulates can cause respiratory issues such as coughing, reduced lung function, lung cancer, asthma, difficulty breathing, and even death. The aim of this study is to analyze the environmental health risks of PM2.5, PM10, and TSP on market workers who are directly exposed to ambient air pollution around Pasar 16 Ilir in Palembang City. Method: The level of acceptable health risk or to estimate the health risk from exposure to PM2.5, PM10, and TSP can be calculated using Environmental Health Risk Analysis (EHRA). The human population taken in this study consisted of market workers working around Pasar 16 Ilir in Palembang City, with a total of 102 respondents selected purposively from 5 measurement points, which were points with higher human activity. PM2.5, PM10, and TSP measurements were taken every morning, afternoon, and evening for 5 working days using a Met One E-Sampler device. Result: The research results indicate that the PM10 variable has a health risk impact on market workers with a value of 1.732 or RQ>1, whereas PM2.5 and TSP have RQ values <1. Conclusion: Exposure to PM10 has health risk impacts on market workers, whereas exposure to PM2.5 and TSP does not have health impacts on market workers.